2017
DOI: 10.1063/1.5003340
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of reentrant driver localization to electrophysiological parameter variability in image-based computational models of persistent atrial fibrillation sustained by a fibrotic substrate

Abstract: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia, causing morbidity and mortality in millions worldwide. The atria of patients with persistent AF (PsAF) are characterized by the presence of extensive and distributed atrial fibrosis, which facilitates the formation of persistent reentrant drivers (RDs, i.e., spiral waves), which promote fibrillatory activity. Targeted catheter ablation of RD-harboring tissues has shown promise as a clinical treatment for PsAF, but the outcomes remain sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 44 publications
(69 reference statements)
5
63
1
Order By: Relevance
“…For example, our results validate the effort to develop a deterministic or a nonlinear stochastic model to simulate AF. [6][7][8][9][10] In addition, our results justify the use of nonlinear dynamical tools to describe AF properties.…”
Section: B Determinism Of Atrial Fibrillationsupporting
confidence: 61%
“…For example, our results validate the effort to develop a deterministic or a nonlinear stochastic model to simulate AF. [6][7][8][9][10] In addition, our results justify the use of nonlinear dynamical tools to describe AF properties.…”
Section: B Determinism Of Atrial Fibrillationsupporting
confidence: 61%
“…In the case of fibrotic atria, propagation is constrained by the distribution of fibrosis through the physiological and/or structural changes made to the tissue, depending on the formulation of the implementation method. Previous clinical and computational studies have shown that tissue areas with higher fibrosis density attract more re-entrant activity than other areas (Deng et al, 2017 ; Cochet et al, 2018 ), but the trajectories can change, particularly when there are several fibrotic areas close to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al ( 2017 ) investigated the sensitivity of rotor location to variations in APD and CV, for simulations incorporating fibrosis modeled with modified ionic and conductivity properties. In their simulations, rotors were overwhelmingly located in border regions between fibrotic and healthy tissue regardless of APD and CV values; however, the specific border regions that contained rotors varied depending on the APD and CV parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although much is still unknown about the role of structural and electrophysiological heterogeneities in AF, computational studies have contributed to the systematic characterization of the mechanisms of arrhythmogenesis. In some cases, these have highlighted the importance of patient-specific aspects for clinical therapy, as, for instance, the role of patient-specific fibrosis patterns for guiding catheter ablation procedures ( McDowell et al, 2015 ; Boyle et al, 2016 ; Deng et al, 2017 ; Cochet et al, 2018 ).…”
Section: In Silico Atrial Modelingmentioning
confidence: 99%